Factors Associated with Sleep Quality in Final Year Students - Huma, Christiano; Junias, Marylin S; Boeky, Daniela L. A. (Universitas Nusa Cendana, 2023)
This study was conducted to determine several factors related to sleep quality in students who are working on a thesis at FKM Undana. This research is a quantitative research using a cross sectional design. The population in this study were FKM Undana students who were working on a thesis totaling 283 students. Based on the results of Key's research that there is a significant relationship between physical, physical activity, stress, and sleep quality and there is no relationship between environmental factors and sleep quality. The sample of this research is the final year students of FKM Undana. Suggestions to students who are working on theses are expected to be able to maintain health, manage stress to get good quality sleep.